A MULTI-ITEM INVENTORY MODEL WITH VARIOUS DEMAND FUNCTIONS CONSIDERING DETERIORATION AND PARTIAL BACKLOGGING - Joviani, Tania; Lesmono, Dharma; Limansyah, Taufik (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
Inventory management is an important thing to be considered in order to run the activities of a company smoothly. By considering deterioration factor, partial backlogging policy and different type of demand functions, we develop a mathematical model for multi-item inventory system. In this paper, three inventory models with constant deterioration, partial backlogging, with various demand functions are developed. We consider inventory-dependent demand, time-dependent demand and exponential demand function in each model. In addition, we also consider the replenishment policies for those three items, viz. individual replenishment, joint replenishment and combination both individual and joint replenishments. Sensitivity analysis of the models is also performed, and we found that the ordering cost greatly affects the total inventory cost when comparing the available replenishment policies.